Information on sorghum seeds (Shi gnouma de bè senekela ka sôrôkofô) - International Institute of Tropical Agriculture (International Livestock Research Institute, 2018)
Episode one of a radio program series by the Africa RISING program in Bambara dialect that is spoken in southern Mali. In this episode which aired on KAFO KAN radio on 20 October 2017, farmers are being provided with relevant information about dual purpose sorghum seeds. Discussions in the episode revolve around the qualities of a good seed, climate change and seed history. This radio program was produced as part of Africa RISING activity - use of Interactive radio to scale-up agriculture and nutrition technologies in Africa RISING Mali.